2002
DOI: 10.1353/jsh.2003.0037
|View full text |Cite
|
Sign up to set email alerts
|

"What We Want Is Good, Sober Men:" Masculinity, Respectability, and Temperance in the Railroad Brotherhoods, c. 1870-1910

Abstract: On the morning of 13 December 1907, locomotive engineer J. A. Yarbrough reported for duty switching freight cars in the Atlanta yards of the Central of Georgia Railroad. However, the yardmaster discovered that Yarbrough had spent some time in a nearby tavern and was drunk, and dismissed him from the service. The incident came to the attention of the union that represented Yarbrough, Division 210 of the Brotherhood of Locomotive Engineers. The Division appointed an investigating committee that interviewed Yarbr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
1

Year Published

2006
2006
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(5 citation statements)
references
References 41 publications
0
4
0
1
Order By: Relevance
“…Instead, a more common theme was that of the “family wage,” that drew on de‐materialized ideas of maternalism, as well as stereotypical notions of masculinity and femininity to claim that working‐class men should earn enough to support the family, including a stay‐at‐home wife. In this sense, rhetoric that highlighted women's wage‐work as a source of dependency thus reinforced the claims for autonomy and higher wages for working‐class men (Hallgrimsdottir ; Taillon ). In addition, because working‐class activists adopted and adapted middle‐class feminist language in this construction, they not only participated in middle‐class articulations of gendered citizenship but also colluded in the creation of the working‐class woman as a second‐class citizen.…”
Section: Resultsmentioning
confidence: 99%
“…Instead, a more common theme was that of the “family wage,” that drew on de‐materialized ideas of maternalism, as well as stereotypical notions of masculinity and femininity to claim that working‐class men should earn enough to support the family, including a stay‐at‐home wife. In this sense, rhetoric that highlighted women's wage‐work as a source of dependency thus reinforced the claims for autonomy and higher wages for working‐class men (Hallgrimsdottir ; Taillon ). In addition, because working‐class activists adopted and adapted middle‐class feminist language in this construction, they not only participated in middle‐class articulations of gendered citizenship but also colluded in the creation of the working‐class woman as a second‐class citizen.…”
Section: Resultsmentioning
confidence: 99%
“…The connection between the norms of hegemonic masculinity and the goal of total abstinence that took place in the 19th century within the temperance movement (Taillon, 2002) is important to be a subject of further study and critical reflection. It is important to reflect on whether the dominant representations of hegemonic masculinity in the field of addiction treatment also influence the “acceptable” content of recovery for all people with similar problems.…”
Section: Discussionmentioning
confidence: 99%
“…This is the profile of a healthy man who completely abstains from substance use, is hard-working and consistent. This recovery profile has been influenced by the temperance movement in the field of addiction (Stolberg, 2006; Taillon, 2002), which equates recovery with abstinence and essentially disputes harm reduction and controlled use as a tenable goal (Alexander and Van De Wijngaart, 1997; Peele, 1993). It has also been observed that dimensions of hegemonic masculinity are embodied into the recovery process.…”
Section: Dominant/hegemonic Masculinity and Addiction: Emerging Quest...mentioning
confidence: 99%
“…The Big Four railroad brotherhoods began as fraternal efforts to provide skilled railroad workers with sickness and injury benefits (see Arnesen, 1994;Taillon, 2001Taillon, , 2002Taillon, , 2009. At their outset, the Brotherhood of Locomotive Engineers (BLE; founded in 1863), the Order of Railway Conductors (ORC; 1868), the Brotherhood of Locomotive Firemen (and Enginemen by 1907) (BLFE; 1873), and the Brotherhood of Railroad Trainmen (BRT; 1883) were generally conservative, viewed strikes as a dangerous last resort, and were more apt than other unions to work closely with employers to achieve their goals.…”
Section: The Railroad Brotherhoodsmentioning
confidence: 99%